External financing and investment in firms (1990- 2020) - Onyinyechi, Mbagwu (International research journal of management, IT and social sciences, 2021)
The study examined the relationship between external financing and investment in firms in Nigeria for the duration of 1990-2019. To achieve the main objective of the study, investment in firms which is the dependent variable was proxy with Industrial Growth (INDG) while the external financing as the independent variable was measure with External Debt Stock (EDS), Foreign Direct Investment (FDI), Official Development Assistance (ODA) and Foreign Portfolio Investment (FPI). This study made use of Ex-post facto research design and secondary source of data (time series data), from the CBN statistical bulletin and Annual Report for the period 1990-2019. The stationary and normality tests will be carried out to ascertain the set data will give accurate regression results since the data for the study are annual time series data. The study adopted several techniques of data analysis such as descriptive statistics, correlation, and multiple regression tool of analysis with the aid of E-VIEW 9.0 statistical package was used to analyze the data because this technique was used to establish the kind of relationship that exists between the independent variables and the dependent variable used in the study.